Municipalidades y participation local en la gestion forestal en Bolivia - Pacheco, P. (CIFOR and IDRC, 2003)
This chapter analyses the model of decentralization of forest management in Bolivia, and assess its main outcomes. Though significant functions were delegated to municipalities regarding forest resources such as control of forest crime, monitoring of forest management, delimitation and allocation of municipal reserves, the central state has reserved by itself some key functions regarding forest resources allocation and formulation of forest regulations. Besides the powers delegated to local governments, there are other factors that influence on decentralization such as the political economy of municipalities, the social pressures of local forest users over the local government, and the property regimes. Those conditioning factors affect the institutional capacity of local governments to deal with forest management which is also influenced by the amount of forest resources municipalities spend on their municipal forest units, the human resources capacities, and the degrees of transparency in decision making within local governments. The interactions of all those factors define the diverse results that decentralization has in practice for people and forest resources.